Positive lithium supplement pole piece slurry, preparation method of pole piece and battery formation method

By constructing a corrosive battery model in lithium iron phosphate batteries, and using the chemical characteristics of lithium iron phosphate to decompose lithium oxalate, the problem of excessive decomposition potential of lithium oxalate is solved, the battery capacity and cycle life is improved, and the electrolyte usage and battery cost are reduced.

CN119695079AActive Publication Date: 2025-03-25UNIV OF SCI & TECH BEIJING
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411882080.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-25
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The decomposition potential of lithium oxalate in lithium iron phosphate battery system is too high, resulting in excessive reaction of the electrolyte, affecting the battery capacity and cycle life.

Method used

By constructing a nano-micrometer-scale corrosive battery model in the positive electrode sheet, the chemical characteristics of lithium iron phosphate after deliquefaction of lithium iron phosphate electrochemically/chemically catalyzed to decompose lithium oxalate, reducing its decomposition potential to 3.5V.

Benefits of technology

It realizes efficient decomposition of lithium oxalate, improves the capacity and cycle life of lithium-ion batteries, and reduces the amount of electrolyte and the cost of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695079A_ABST
    Figure CN119695079A_ABST
Patent Text Reader

Abstract

The invention provides positive electrode lithium supplement pole piece slurry, a preparation method of a pole piece and a battery formation method, and belongs to the technical field of lithium ion batteries. Comprising the following steps: preparing a lithium oxalate dispersion liquid; mixing lithium iron phosphate powder with a conductive agent, and then adding the lithium oxalate dispersion liquid and a binder to prepare slurry; the particle size of lithium oxalate in the lithium oxalate dispersion liquid and the particle size of the lithium iron phosphate powder meet the condition that the ratio of D50LFP to D50LCO is 100: (15-25), the range of D50LFP is 1.0-2.0 microns, D50LFP is the D50 particle size of lithium iron phosphate, and D50LCO is the D50 particle size of lithium oxalate. On the basis of the theoretical decomposition potential of lithium oxalate, a plurality of nano-micron scale corrosion battery models are constructed in a positive pole piece, and the lithium oxalate is subjected to electrochemical / chemical catalytic decomposition by utilizing the chemical characteristics of iron phosphate after lithium removal of lithium iron phosphate, so that the decomposition potential of the lithium oxalate is reduced to 3.5 V.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-ion batteries, and in particular relates to a positive-electrode lithium-supplementing pole piece slurry, a pole piece preparation method and a battery formation method. Background Art

[0002] Among many lithium batteries, lithium iron phosphate batteries have high safety, long cycle life, abundant resources and low cost. They are the material system with the lowest comprehensive cost among all commercial lithium-ion battery cathode materials and are suitable for large-scale use. However, due to the loss of active lithium in the negative electrode, lithium iron phosphate batteries are difficult to perform at their best. The capacity and cycle life of lithium iron phosphate batteries can be significantly improved through a positive electrode lithium replenishment strategy with a short process flow and excellent industrial compatibility. As a sacrificial salt lithium replenisher, lithium oxalate has a high specific capacity and the characteristics of no by-products during decomposition, which has a high practical application value. Lithium oxalate not only decomposes and replenishes the lithium ions lost by the battery, but its decomposition product carbon dioxide can also optimize the composition and morphology of the solid electrolyte membrane on the negative electrode side, further improving the cycle life of the battery. However, lithium oxalate has a very high decomposition potential (4.7V) and is not suitable for lithium iron phosphate battery systems. In order to prevent excessive charging voltage from causing excessive reaction of the electrolyte, the decomposition voltage of lithium oxalate must be reduced. Therefore, reducing the decomposition voltage of lithium oxalate has become a hot topic in the research of improving the capacity and cycle life of lithium-ion batteries.

[0003] The reason why lithium oxalate has a high decomposition potential is due to its poor kinetic behavior. The conventional method to reduce the potential is to modify the surface by coating or adding a catalyst, and to reduce the decomposition voltage by increasing the conductivity of lithium oxalate and reducing the activation energy of the reaction. However, this method introduces too much inactive material into the battery, increasing the mass and volume of the battery. Compared with the increased capacity, the improvement in the energy density of the battery is limited. Secondly, the preparation cost of this complex three-dimensional nanoparticle material is high, and it cannot give full play to the low-cost advantage of lithium iron phosphate batteries. It is more inclined to basic research and is not suitable for the actual production and application of batteries. Summary of the invention

[0004] To solve the above problems, the present invention provides a positive electrode lithium supplement pole piece slurry, a pole piece preparation method and a battery formation method. Starting from the theoretical decomposition potential of lithium oxalate, multiple nano-micrometer scale corrosion battery models are constructed in the positive electrode pole piece. The chemical properties of iron phosphate itself after lithium iron phosphate is delithiated are utilized to electrochemically / chemically catalytically decompose lithium oxalate, thereby reducing the decomposition potential of lithium oxalate to 3.5V.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0006] On the one hand, the present invention provides a method for preparing a positive electrode lithium supplement pole piece slurry, comprising the following steps: preparing a lithium oxalate dispersion; mixing lithium iron phosphate powder with a conductive agent and then adding the lithium oxalate dispersion and a binder to prepare a slurry; the particle sizes of the lithium oxalate in the lithium oxalate dispersion and the lithium iron phosphate powder satisfy: D 50 LFP :D 50 LCO =100:(15-25), the D 50 LFP The range is 1.0-2.0um, where D 50 LFP D for lithium iron phosphate 50 Particle size, D 50 LCO D for lithium oxalate 50 Particle size.

[0007] Furthermore, the mass ratio of lithium oxalate to solvent in the lithium oxalate dispersion is 0.15-0.25; and the solvent is selected from one or more of N-methylpyrrolidone, N,N-dimethylformamide, ethanol, isopropanol, acetone, toluene or n-hexane.

[0008] Furthermore, the mass percentage of the binder is 4%-6%, and the binder is selected from one or more of polyvinylidene fluoride, polyvinyl alcohol, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, and polypropylene.

[0009] Furthermore, the mass ratio of the lithium iron phosphate powder to the conductive agent is 3.5-4.5; the conductive agent is selected from one or more of porous carbon, SuperP, acetylene black, carbon nanotubes, carbon black, Ketjen black, graphene, and MXenes.

[0010] Furthermore, the ratio of the amount of the lithium oxalate dispersion added to the mass of the lithium iron phosphate powder is 1:(1.3-5.3).

[0011] Furthermore, the lithium iron phosphate powder and the conductive agent are mixed by a centrifugal planetary mixer at a speed of 300-600 r / min for 5-10 min, a binder and a lithium oxalate dispersion are added, the speed is maintained at 400-700 r / min for 5-10 min, and then the speed is maintained at 1200-2000 r / min for 40-80 min.

[0012] On the other hand, the present invention provides a method for preparing a positive lithium-replenishing electrode sheet, wherein the positive lithium-replenishing electrode sheet slurry is prepared by the above-mentioned preparation method; the slurry is coated and then dried to obtain a positive electrode sheet blank; and the positive electrode sheet blank is rolled to obtain the positive lithium-replenishing electrode sheet.

[0013] Furthermore, the reduction rate of the positive electrode sheet blank during rolling is 30%-40%.

[0014] On the other hand, the present invention provides a positive electrode lithium replenishing pole piece, and the positive electrode lithium replenishing pole piece is prepared by the above-mentioned preparation method.

[0015] On the other hand, the present invention provides a lithium-ion battery formation method, in which the above-mentioned positive electrode lithium-supplementing electrode sheet is used as the positive electrode to assemble a lithium-ion battery; the formation system is: constant current charging, the current size is 14-17mA / g, and the limiting voltage is 3.75-4.5V; constant current discharge current size is 14-17mA / g, the termination voltage is 2.7V-2.0V, and then exhaust and final sealing are performed.

[0016] The beneficial effects brought by the technical solution provided by the embodiment of the present invention include:

[0017] After the positive lithium-supplementing electrode slurry provided by the present invention is prepared into a battery, the chemical properties of the iron phosphate phase itself after lithium iron phosphate is delithiated are used to catalytically decompose lithium oxalate to achieve 3.5V decomposition during the formation process, and the product carbon dioxide is used to optimize the SEI on the negative electrode side during the first cycle formation process of the battery. This method does not require the introduction of additional inactive materials (such as catalysts), and the battery has higher mass and volume energy density. The decomposition of lithium oxalate at 3.5V not only improves the capacity of the battery, but also the product carbon dioxide optimizes the SEI on the negative electrode side to improve the cycle life of the battery. Similarly, the decomposition of lithium oxalate at 3.5V reduces the side reactions of the electrolyte and reduces the amount of electrolyte used. The lower limiting voltage reduces the energy consumption in the formation process and reduces the cost of the battery. However, it should be made clear that in order to achieve the catalytic decomposition of lithium oxalate by the iron phosphate generated by the subsequent chemical formation, the particle size of lithium oxalate and lithium iron phosphate powders must meet the specified conditions of the present invention. Otherwise, even if lithium oxalate and lithium iron phosphate are mixed to prepare positive electrode lithium replenishment plates in the prior art, a catalyst needs to be added to achieve the catalytic decomposition of lithium oxalate. The present invention controls the particle size within the above range to achieve a decomposition ratio of lithium oxalate of at least 70%. Compared with the prior art, the lithium replenishment effect can be achieved without adding a catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0019] Figure 1 This is a SEM image of the positive lithium supplementation electrode prepared in Example 1 of the present invention;

[0020] Figure 2 The first cycle charge and discharge curves of the positive lithium supplement electrode sheet of Example 1 of the present invention at a limiting voltage of 4.2V and the positive electrode sheet prepared in Comparative Example 1 at a limiting voltage of 4.2V;

[0021] Figure 3 Cycling capacity curves of the positive lithium supplementing electrode sheet of Example 1 of the present invention at a limiting voltage of 4.2V and the positive electrode sheet prepared in Comparative Example 1 at a limiting voltage of 4.2V;

[0022] Figure 4 The first cycle charge and discharge curves of the positive lithium supplement electrode sheet of Example 1 of the present invention at a limiting voltage of 4.5V and the positive electrode sheet prepared in Comparative Example 1 at a limiting voltage of 4.2V;

[0023] Figure 5 The cycle capacity curves are of the positive lithium supplementation electrode sheet of Example 1 of the present invention at a limiting voltage of 4.5V and of the positive electrode sheet prepared in Comparative Example 1 at a limiting voltage of 4.2V. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.

[0025] The embodiment of the present invention provides a method for preparing a positive electrode lithium supplement pole piece slurry, comprising the following steps: preparing a lithium oxalate dispersion; mixing lithium iron phosphate powder with a conductive agent and then adding the lithium oxalate dispersion and a binder to prepare a slurry; the particle sizes of the lithium oxalate in the lithium oxalate dispersion and the lithium iron phosphate powder satisfy: D 50 LFP :D 50 LCO =100:(15-25), the D 50 LFP The range is 1.0-2.0um, where D 50 LFP D for lithium iron phosphate 50 Particle size, D 50 LCO D for lithium oxalate 50 Particle size. Preferably, D 50 LFP :D 50 LCO =100:20, D 50 LFP It is 1.5um.

[0026] After the positive electrode lithium supplementation pole piece slurry prepared by the above-mentioned preparation method is prepared into a battery, the chemical properties of the iron phosphate phase itself after lithium iron phosphate is delithiated are used to catalytically decompose lithium oxalate to achieve 3.5V decomposition during the formation process, and the product carbon dioxide is used to optimize the SEI on the negative electrode side during the first cycle formation process of the battery. This method does not require the introduction of additional inactive materials (such as catalysts), and the battery has higher mass and volume energy density. The decomposition of lithium oxalate at 3.5V not only improves the capacity of the battery, but also the product carbon dioxide optimizes the SEI on the negative electrode side to improve the cycle life of the battery. Similarly, the decomposition of lithium oxalate at 3.5V reduces the side reactions of the electrolyte, reduces the amount of electrolyte used, and the lower limiting voltage reduces the energy consumption in the formation process, reducing the cost of the battery. However, it should be made clear that in order to achieve the catalytic decomposition of lithium oxalate by the iron phosphate generated by the subsequent chemical formation, the particle size of lithium oxalate and lithium iron phosphate powders must meet the above conditions. Otherwise, even if lithium oxalate and lithium iron phosphate are mixed to prepare the positive electrode lithium replenishment electrode, as in the prior art, a catalyst needs to be added to achieve the catalytic decomposition of lithium oxalate. The present invention controls the particle size within the above range to achieve a decomposition ratio of lithium oxalate of at least 70%. Compared with the prior art, the lithium replenishment effect can be achieved without adding a catalyst.

[0027] The mass ratio of lithium oxalate to solvent in the lithium oxalate dispersion is 0.15-0.25; the solvent is selected from one or more of N-methylpyrrolidone, N,N-dimethylformamide, ethanol, isopropanol, acetone, toluene or n-hexane. Specifically, the lithium oxalate powder and the solvent are mixed by ball milling, preferably using a planetary ball mill, and the ball milling process is: ball milling at a speed of 1300-1500r / min for 8-12h to reduce the particle size of the lithium oxalate powder. For illustration, N-methylpyrrolidone (NMP) is selected as the solvent in the embodiment of the present invention, and the final finished lithium oxalate dispersion has suitable fluidity and is evenly dispersed.

[0028] The mass percentage of the binder is 4%-6%, and the binder is selected from one or more of polyvinylidene fluoride, polyvinyl alcohol, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, and polypropylene. Its main function is to control the viscosity of the slurry on the one hand, and on the other hand, after mixing with the positive electrode material, it is beneficial for the positive electrode slurry to form a continuous, dense and uniform positive electrode material film layer on the surface of the current collector. The solvent is selected from one or more of N-methylpyrrolidone, N,N-dimethylformamide, ethanol, isopropanol, acetone, toluene or n-hexane. For illustration, polyvinylidene fluoride (PVDF) is selected as the binder and N-methylpyrrolidone (NMP) is used as the solvent in the embodiment of the present invention. Weigh the corresponding binder and solvent according to the mass percentage, and mix them by magnetic stirring. Preferably, the magnetic stirring time is 8-12h.

[0029] The mass ratio of the lithium iron phosphate powder to the conductive agent is 3.5-4.5; the conductive agent is selected from one or more of porous carbon, Super P, acetylene black, carbon nanotubes, carbon black, Ketjen black, graphene, and MXenes. Preferably, Super P-Li and Ketjen black (KB) in the same mass ratio are used as the conductive agent. MXenes are a class of transition metal compounds, represented by the chemical formula M n+1 X n T x , wherein M is selected from one or more transition metal elements, X is selected from one, two or three of carbon, nitrogen or boron elements, n is between 1 and 4, T x The addition of a conductive agent to the lithium supplement slurry provides two functions: one is to conduct electricity to improve the conductivity of the positive electrode material layer in the positive electrode sheet; the other is to absorb the byproduct S of the lithium supplement agent. x 2- , to avoid the loss of lithium ions.

[0030] The ratio of the added amount of the lithium oxalate dispersion to the mass of the lithium iron phosphate powder is 1:(1.3-5.3). Preferably, the added amount of the binder is 1.8-2.2 times the total mass of the lithium iron phosphate and the conductive agent.

[0031] The lithium iron phosphate powder and the conductive agent are mixed with a centrifugal planetary mixer, maintained at a speed of 300-600r / min for 5-10min, and a binder and a lithium oxalate dispersion are added, maintained at a speed of 400-700r / min for 5-10min, and then maintained at a speed of 1200-2000r / min for 40-80min. It should be pointed out that the mixing method has a great influence on the mixing effect of lithium oxalate and lithium iron phosphate. In the early stage, various components are mixed at a lower speed and a shorter time to improve the uniformity of various components. At this time, there is a slight agglomeration phenomenon in lithium oxalate. Subsequently, a higher speed and a longer time are used for high-energy ball milling to interact the agglomerated lithium oxalate with the lithium iron phosphate, so that the lithium oxalate is attached to the surface of the lithium iron phosphate to improve the contact between the smaller lithium oxalate and the larger lithium iron phosphate. After the lithium iron phosphate is delithiated, the iron phosphate can effectively contact the lithium oxalate to improve the catalytic decomposition ability of the lithium oxalate.

[0032] An embodiment of the present invention also provides a method for preparing a positive lithium-replenishing electrode sheet, comprising: preparing a positive lithium-replenishing electrode sheet slurry by the above-mentioned preparation method; applying the slurry and then drying it to obtain a positive electrode sheet blank, and rolling the positive electrode sheet blank to obtain the positive lithium-replenishing electrode sheet.

[0033] Specifically, the electrode is coated on aluminum foil by flat coating and then dried, and the electrode coating thickness is 100-250um; the drying process is to keep warm at 100-125℃ for 20-50min, and then dry in a vacuum oven at 60-85℃ for 6-12h. This electrode drying system can effectively prevent the electrode cracking caused by too fast drying speed, and also prevent the local segregation of lithium oxalate due to too slow drying speed, so that the electrode surface density is uniform, especially for the situation where it is difficult to catalytically decompose lithium oxalate using iron phosphate in this application. A positive electrode lithium supplement electrode for 3.5V decomposition of lithium oxalate is obtained by rolling the dried electrode using a double roller machine. The thickness of the positive electrode blank after rolling is 60%-70% before rolling, that is, the reduction rate is 30%-40%. The tight connection between the electrode particles after rolling is conducive to the catalytic effect of iron phosphate on lithium oxalate.

[0034] The embodiment of the present invention further provides a positive electrode lithium replenishing pole piece, and the positive electrode lithium replenishing pole piece is prepared by the above-mentioned preparation method.

[0035] The embodiment of the present invention also provides a formation method of a lithium-ion battery, including assembling a lithium-ion battery using the above-mentioned positive electrode lithium supplementation electrode sheet; the formation system is: constant current charging, the current size is 14-17mA / g, and the limiting voltage is 3.75-4.5V; the constant current discharge current size is 14-17mA / g, the termination voltage is 2.7V-2.0V, and then exhaust and final sealing are performed. The formation system is very critical. The formation system affects the effect of lithium iron phosphate delithiation, and the lithium delithiation effect of lithium iron phosphate affects the catalytic decomposition of lithium oxalate, such as the uniformity and amount of iron phosphate generation. If the amount generated is small, the ability to catalytically decompose lithium oxalate is weak and lithium cannot be effectively supplemented, while if the amount generated is large, the electrode activity is affected; secondly, the advantage of the formation system is that the exhaust is performed after the first complete cycle, and the carbon dioxide in the battery is conducive to the formation of a stable negative electrode surface SEI, which improves the cycle performance of the battery.

[0036] Specifically, the positive electrode lithium supplement pole piece prepared by decomposing lithium oxalate at 3.5V is used as the positive electrode, the graphite pole piece is used as the negative electrode, the 1mol / L lithium hexafluorophosphate electrolyte, and the solvent is dimethyl carbonate (DMC), ethylene carbonate (EC) and ethyl methyl carbonate (EMC) with a volume ratio of 1:1:1. The assembled battery is placed in a constant temperature box at 30°C for 24 hours to allow the electrolyte to fully infiltrate, and the battery is charged and discharged by a constant current charge and discharge method in a constant temperature box at 30°C. The vacuum degree of the battery injection is -20 to -50Kpa, and the vacuum degree during sealing is -70 to -100Kpa. The advantage is that negative pressure injection is conducive to the infiltration between the electrolyte and the positive electrode particles, reducing the impedance of lithium ion diffusion.

[0037] In order to better illustrate the embodiments of the present invention, the present invention is further described in detail below through specific examples.

[0038] Example 1

[0039] The embodiment of the present invention provides a positive electrode lithium supplementation pole piece slurry, a pole piece preparation method and a battery formation method, including:

[0040] S1: preparing a lithium oxalate dispersion. Lithium oxalate powder and NMP are weighed in a ratio of lithium oxalate to solvent of 0.25, placed in a ball milling jar, sealed, and ball milled on a planetary ball mill for 10 hours before being taken out.

[0041] S2: Mix the lithium iron phosphate powder with the conductive agent and then add the lithium oxalate dispersion and the binder to prepare a slurry. 50 The conductive agent is added according to the mass ratio of lithium iron phosphate powder to conductive agent of 4, D 50 LCO The conductive agent is 0.23um, and the conductive agent is made of Super P Li and Ketjen Black of the same mass, which are placed in a mixing tank and mixed evenly; then the binder is added in an amount of 2 times the total mass of lithium iron phosphate and the conductive agent, and the binder is a binder with a mass fraction of 5wt% prepared by mixing PVDF powder and NMP solution, and the lithium oxalate dispersion is added in a mass ratio of 1:2.2 to the lithium iron phosphate powder, and the speed is maintained at 500r / min for 5min, and then the speed is maintained at 1200r / min for 60min. The slurry is obtained.

[0042] S3 uses a flat plate automatic coating machine to coat the prepared slurry on aluminum foil with a coating thickness of 100um, a drying temperature of 120°C, a heating time of 40min after reaching the temperature, and then puts it into a vacuum oven at 80°C for 12h. Then the electrode is rolled, and the thickness before rolling is measured to be 80um. Rolling is performed at a reduction rate of 40%, and rolling is performed multiple times until the electrode thickness is 48um (±5um), thus obtaining the positive electrode replenishing lithium electrode. The prepared positive electrode replenishing lithium electrode is as follows Figure 1 shown.

[0043] S4 prepares two identical lithium-ion batteries. After selecting the graphite negative electrode according to the surface capacity of the prepared positive electrode, the prepared positive electrode is stacked, packaged with aluminum-plastic film, and moved into the glove box for liquid injection. The liquid injection vacuum is -45Kpa, and the packaging vacuum is -90Kpa. The packaged battery is placed in a constant temperature box at 30℃ for 24 hours. The two lithium-ion batteries are then charged with a current of 15mA / g to a limit voltage of 4.2V and 4.5V respectively. After being left for 2 minutes, they are discharged with the same current to 2.0V.

[0044] like Figure 2 and 3As shown, the prepared lithium-ion battery has a first-cycle charge capacity of 180.74 mAh / g at 2.0-4.2 V and 0.1 C rate, a first-cycle discharge capacity of 131.23 mAh / g, a delithiation potential platform of about 3.5 V, and a cycle efficiency of 82.42% for 200 cycles at 1 C.

[0045] like Figure 4 and 5 As shown, the prepared lithium-ion battery has a first-cycle charge capacity of 206.49 mAh / g at 2.0-4.5 V and 0.1 C rate, a first-cycle discharge capacity of 140.03 mAh / g, and a delithiation potential platform of approximately 3.5 V (decomposition ratio: 51%) and 4.4 V (decomposition ratio: 49%). The cycle efficiency of 200 cycles at 1 C is 68.67%.

[0046] Example 2

[0047] The embodiment of the present invention provides a positive electrode lithium supplementation pole piece slurry, a pole piece preparation method and a battery formation method, including:

[0048] S1: preparing a lithium oxalate dispersion. Lithium oxalate powder and NMP were weighed in a ratio of 0.15 between the mass ratio of lithium oxalate and the solvent, placed in a ball milling jar, sealed, and ball milled on a planetary ball mill for 8 hours before being taken out.

[0049] S2: Mix the lithium iron phosphate powder with the conductive agent and then add the lithium oxalate dispersion and the binder to prepare a slurry. 50 The conductive agent is added according to the mass ratio of lithium iron phosphate powder to conductive agent of 3.5. 50 LCO The conductive agent is 0.2um, and the conductive agent is made of Super P Li and Ketjen Black of the same mass, which are placed in a mixing tank and mixed evenly; then the binder is added in an amount of 1.8 times the total mass of lithium iron phosphate and the conductive agent, and the binder is a binder with a mass fraction of 4wt% prepared by mixing PVDF powder and NMP solution, and the lithium oxalate dispersion is added in a mass ratio of 1:1.3 to the lithium iron phosphate powder, and the speed is maintained at 400r / min for 5min, and then the speed is maintained at 1200r / min for 40min. The slurry is obtained.

[0050] S3 uses a flat plate automatic coating machine to coat the prepared slurry on aluminum foil, the drying temperature is 100°C, the heating time after reaching the temperature is 20 minutes, and then put it into a vacuum oven at 60°C for 6 hours. Then the electrode is rolled at a reduction rate of 30% to obtain the positive electrode lithium supplement electrode.

[0051] S4 selects the graphite negative electrode according to the surface capacity of the prepared positive electrode, stacks them, packages them with aluminum plastic film, and moves them into the glove box for liquid injection. The vacuum degree of liquid injection is -20Kpa, and the vacuum degree of packaging is -70Kpa. The packaged battery is placed in a constant temperature box at 30℃ for 24h. Then, a current of 14mA / g is used to charge the battery at a constant current until the limiting voltage is 4.2V, and after 2min of storage, the battery is discharged at the same constant current to 2.0V.

[0052] The prepared lithium-ion battery has a first-cycle charge capacity of 175.25 mAh / g at 2.0-4.2 V and 0.1 C rate, a first-cycle discharge capacity of 126.45 mAh / g, a delithiation potential platform of about 3.5 V, and a cycle efficiency of 79.40% for 200 cycles at 1 C.

[0053] Example 3

[0054] The embodiment of the present invention provides a positive electrode lithium supplementation pole piece slurry, a pole piece preparation method and a battery formation method, including:

[0055] S1: preparing a lithium oxalate dispersion. Lithium oxalate powder and NMP are weighed in a ratio of lithium oxalate to solvent of 0.25, placed in a ball milling jar, sealed, and ball milled on a planetary ball mill for 10 hours before being taken out.

[0056] S2: Mix the lithium iron phosphate powder with the conductive agent and then add the lithium oxalate dispersion and the binder to prepare a slurry. 50 The conductive agent is added according to the mass ratio of lithium iron phosphate powder to conductive agent of 4.5. 50 LCO The conductive agent is 0.4um, and the conductive agent is made of Super P Li and Ketjen Black of the same mass, which are placed in a mixing tank and mixed evenly; then the binder is added in an amount of 2.2 times the total mass of lithium iron phosphate and the conductive agent, and the binder is a binder with a mass fraction of 6wt% prepared by mixing PVDF powder and NMP solution, and the lithium oxalate dispersion is added in a mass ratio of 1:5.3 to the lithium iron phosphate powder, and the speed is maintained at 700r / min for 10min, and then maintained at 2000r / min for 80min. The slurry is obtained.

[0057] S3 uses a flat plate automatic coating machine to coat the prepared slurry on aluminum foil with a coating thickness of 250um, a drying temperature of 125°C, a heating time of 50 minutes after reaching the temperature, and then puts it into a vacuum oven at 85°C for 12 hours. Then, the electrode is rolled at a reduction rate of 40% to obtain the positive electrode lithium supplement electrode.

[0058] S4 selects the graphite negative electrode according to the surface capacity of the prepared positive electrode, stacks the sheets, packages with aluminum plastic film, and moves into the glove box for liquid injection. The vacuum degree of liquid injection is -50Kpa, and the vacuum degree of packaging is -100Kpa. The packaged battery is placed in a constant temperature box at 30℃ for 24h. Then, a current of 17mA / g is used to charge at a constant current until the limiting voltage is 4.2V, and after 2min, it is discharged at the same constant current to 2.0V.

[0059] The prepared lithium-ion battery has a first-cycle charge capacity of 178.56 mAh / g at 2.0-4.2 V and 0.1 C rate, a first-cycle discharge capacity of 129.43 mAh / g, a delithiation potential platform of about 3.5 V, and a cycle efficiency of 80.21% for 200 cycles at 1 C.

[0060] Comparative Example 1

[0061] Different from Example 1, lithium oxalate was not added in this comparative example.

[0062] In step S4, the lithium-ion battery is charged at a constant current of 15 mA / g to a limit voltage of 4.2 V, and then discharged at the same constant current to 2.0 V after being left for 2 minutes.

[0063] like Figure 2-5 As shown, the prepared lithium-ion battery has a first-cycle charge capacity of 167.14 mAh / g at 2.0-4.2 V and 0.1 C rate, a first-cycle discharge capacity of 124.07 mAh / g, and a cycle efficiency of 68.98% after 200 cycles at 1 C.

[0064] Comparative Example 2

[0065] Different from Example 1, in step S2 of this comparative example, lithium iron phosphate D 50 The particle size is 3um, the D of lithium oxalate 50 The particle size is 0.5um.

[0066] The prepared lithium-ion battery has a first-cycle charge capacity of 172.25 mAh / g at 2.0-4.2 V and 0.1 C rate, a first-cycle discharge capacity of 127.51 mAh / g, a delithiation potential platform of about 3.5 V, and a cycle efficiency of 69.25% after 200 cycles at 1 C.

[0067] Comparative Example 3

[0068] Different from Example 1, in step S2 of this comparative example, the lithium iron phosphate D 50 The D of lithium oxalate is 1.5um. 50 The particle size is 0.2um.

[0069] The prepared lithium-ion battery has a first-cycle charge capacity of 178.56 mAh / g at 2.0-4.2 V and 0.1 C rate, a first-cycle discharge capacity of 129.45 mAh / g, a delithiation potential platform of about 3.5 V, and a cycle efficiency of 79.50% for 200 cycles at 1 C.

[0070] Comparative Example 4

[0071] Different from Example 1, in step S2 of this comparative example, the lithium iron phosphate D 50 The D of lithium oxalate is 1.5um. 50 The particle size is 0.4um.

[0072] The prepared lithium-ion battery has a first-cycle charge capacity of 175.56 mAh / g at 2.0-4.2 V and 0.1 C rate, a first-cycle discharge capacity of 127.50 mAh / g, a delithiation potential platform of about 3.5 V, and a cycle efficiency of 76.45% after 200 cycles at 1 C.

[0073] Comparative Example 5

[0074] Different from Example 1, in step S2 of this comparative example, the rotation speed is maintained at 500 r / min for 65 min.

[0075] The prepared lithium-ion battery has a first-cycle charge capacity of 172.45 mAh / g at 2.0-4.2 V and 0.1 C rate, a first-cycle discharge capacity of 127.05 mAh / g, a delithiation potential platform of about 3.5 V, and a cycle efficiency of 70.25% for 200 cycles at 1 C.

[0076] Comparative Example 6

[0077] Different from Example 1, in step S2 of this comparative example, the rotation speed is maintained at 1200 r / min for 65 min.

[0078] The prepared lithium-ion battery has a first-cycle charge capacity of 170.45 mAh / g at 2.0-4.2 V and 0.1 C rate, a first-cycle discharge capacity of 124.98 mAh / g, a delithiation potential platform of about 3.5 V, and a cycle efficiency of 68.06% for 200 cycles at 1 C.

[0079] It can be seen from Example 1 and Comparative Example 1 that the first charge specific capacity and the first cycle discharge specific capacity are greatly increased. Compared with Comparative Example 1 which only uses lithium iron phosphate as the positive electrode, the lithium ion battery prepared in Example 1 has a first cycle discharge specific capacity increased by 7.2mAh / g and a capacity retention rate increased by 13.44% when the limiting voltage is 4.2V; when the limiting voltage is 4.5V, the first cycle discharge specific capacity is increased by 15.93mAh / g, and the capacity is increased by 23.85%. The above effects are achieved by lithium oxalate decomposition and lithium supplementation. It can be seen that the technical solution provided by the present invention can effectively catalyze the decomposition of lithium oxalate using iron phosphate after lithium iron phosphate is removed without adding a catalyst. It can be seen from Example 1 and Comparative Examples 2-4 that the D of lithium iron phosphate is 50 Particle size, and D of lithium iron phosphate and lithium oxalate 50 The ratio of particle size is particularly important. If the particle size of lithium iron phosphate is too large or the ratio of the two is not matched, the iron phosphate after lithium removal cannot effectively catalyze the decomposition of lithium oxalate. It can be seen from Example 1 and Comparative Examples 5-6 that the mixing system has a greater impact on the prepared lithium-ion battery. The reason is that the size of lithium oxalate is relatively small. At low speeds, lithium oxalate has micron-scale agglomeration and cannot effectively contact the surface of iron phosphate; at higher speeds, lithium oxalate is severely segregated, and lithium oxalate is enriched on the surface of some iron phosphates, while the amount of lithium oxalate enriched on the surface of some iron phosphates is very small, resulting in poor catalytic decomposition of lithium oxalate by iron phosphate. Only low speed and high speed and corresponding speed holding time can achieve excellent mixing effect to improve the performance of the prepared battery.

[0080] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a positive electrode lithium supplementation electrode slurry, characterized in that: The steps include: preparing a lithium oxalate dispersion; The lithium iron phosphate powder is mixed with a conductive agent, and then the lithium oxalate dispersion and a binder are added to prepare a slurry; The particle sizes of the lithium oxalate in the lithium oxalate dispersion and the lithium iron phosphate powder satisfy: 50LFP :D 50LCO =100:(15-25), the D 50LFP The range is 1.0-2.0um, where D 50LFP D for lithium iron phosphate 50 Particle size, D 50LCO D for lithium oxalate 50 Particle size.

2. The preparation method according to claim 1, characterized in that: The mass ratio of lithium oxalate to solvent in the lithium oxalate dispersion is 0.15-0.25; The solvent is selected from one or more of N-methylpyrrolidone, N,N-dimethylformamide, ethanol, isopropanol, acetone, toluene or n-hexane.

3. The preparation method according to claim 1, characterized in that: The mass percentage of the binder is 4%-6%, and the binder is selected from one or more of polyvinylidene fluoride, polyvinyl alcohol, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, and polypropylene.

4. The preparation method according to claim 1, characterized in that: The mass ratio of the lithium iron phosphate powder to the conductive agent is 3.5-4.5; The conductive agent is selected from one or more of porous carbon, SuperP, acetylene black, carbon nanotubes, carbon black, Ketjen black, graphene, and MXenes.

5. The preparation method according to claim 1, characterized in that: The ratio of the amount of the lithium oxalate dispersion added to the mass of the lithium iron phosphate powder is 1:(1.3-5.3).

6. The preparation method according to claim 1, characterized in that: The lithium iron phosphate powder and the conductive agent are mixed by a centrifugal planetary mixer at a speed of 300-600 r / min for 5-10 min, a binder and a lithium oxalate dispersion are added, the speed is maintained at 400-700 r / min for 5-10 min, and then the speed is maintained at 1200-2000 r / min for 40-80 min.

7. A method for preparing a positive lithium supplementing electrode sheet, characterized in that: The positive electrode lithium supplement pole piece slurry is prepared by the preparation method described in any one of claims 1 to 6; The slurry is coated and then dried to obtain a positive electrode sheet blank, and the positive electrode sheet blank is rolled to obtain the positive electrode lithium supplementing sheet.

8. The preparation method according to claim 7, characterized in that: The reduction rate of the positive electrode sheet blank during rolling is 30%-40%.

9. A positive electrode lithium supplementation electrode, characterized in that: The positive electrode lithium supplementation electrode sheet is prepared by the preparation method of claim 7 or 8.

10. A lithium ion battery formation method, characterized in that A lithium-ion battery is assembled using the positive electrode lithium supplement electrode sheet of claim 9 as the positive electrode; The formation system is: constant current charging, the current size is 14-17mA / g, the limiting voltage is 3.75-4.5V; constant current discharge current size is 14-17mA / g, the termination voltage is 2.7V-2.0V, and then exhaust and final sealing are carried out.

Citation Information

Patent Citations

  • Modified lithium iron phosphate composite material, positive electrode material and preparation method thereof

    CN113097455A

  • Positive plate as well as preparation method and application thereof

    CN114094040A

  • Positive electrode lithium supplement agent, positive electrode lithium supplement pole piece prepared from positive electrode lithium supplement agent and lithium ion battery prepared from positive electrode lithium supplement agent

    CN115764010A

  • Positive electrode lithium supplement additive and preparation method and application thereof

    CN117154100A

  • Composite lithium supplementing material as well as preparation method and application thereof

    CN118117092A